Estrés agudo y su influencia en un paciente que padece insuficiencia renal - Veloz Holguin, Valeria Nicole (2020)
The present case study has as its theme “acute stress and its influence on a patient suffering from renal insufficiency” with the aim of establishing the factors that lead to acute stress in a patient undergoing hemodialysis treatment, in the same way it is investigated in the different influences that this disease has on the patient and also the way in which it affects these in his life since through psychological evaluations he intends to help improve his quality of life. The reference that was obtained for the content of this study was applied by means of psychological tests and tools that consist of: interviews, clinical histories, observation, Hamilton's anxiety scale tests and Davidson's trauma scale which were fundamentally based for the stated purpose. Favorable results were obtained, since with the scientific contributions of the authors they were very helpful in establishing each influential factor in a patient with renal insufficiency. Similarly, at the conclusion of this study of this case by means of the applied psychological techniques I lead to the diagnosis identifying that it presents a moderate acute stress, where the patient presents recurrent negative thoughts affecting his quality of life, whether mental or physical.